A detailed study on understanding glycopolymer library and Con A interactions. Issue 12 (13th March 2013) - Gou, Yanzi; Geng, Jin; Richards, Sarah‐Jane; Burns, James; Remzi Becer, C.; Haddleton, D. M.
ABSTRACT Synthetic glycopolymers are important natural oligosaccharides mimics for many biological applications. To develop glycopolymeric drugs and therapeutic agents, factors that control the receptor‐ligand interaction need to be investigated. A library of well‐defined glycopolymers has been prepared by the combination of copper mediated living radical polymerization and CuAAC click reaction via post‐functionalization of alkyne‐containing precursor polymers with different sugar azides. Employing Concanavalin A as the model receptor, we explored the influence of the nature and densities of different sugars residues (mannose, galactose, and glucose) on the stoichiometry of the cluster, the rate of the cluster formation, the inhibitory potency of the glycopolymers, and the stability of the turbidity through quantitative precipitation assays, turbidimetry assays, inhibitory potency assays, and reversal aggregation assays. The diversities of binding properties contributed by different clustering parameters will make it possible to define the structures of the multivalent ligands and densities of binding epitopes tailor‐made for specific functions in the lectin‐ligand interaction. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 2588–2597